Uncertainty analysis in the assessment of long-term noise indicators - Batko, W.; Bal-Pyrcz, R. (Archives of Acoustics, 2006)
This study addresses the assessment conditions of long-term noise indicators based on irregular noise monitoring data. Variations of L_ DEN estimates (day – evening – night noise indicator) on different days of the week were examined. Two hypotheses are verified: that mean estimates shall be identical on all days of the week and that variances of thus obtained estimates are homogeneous. The data for statistical analyses were noise levels recorded in one year by an on-line noise monitoring system in Kraków.